2021
DOI: 10.1016/j.tranon.2020.100886
|View full text |Cite
|
Sign up to set email alerts
|

5-Aminolevulinic acid for fluorescence-guided surgery in pancreatic cancer: Cellular transport and fluorescence quantification studies

Abstract: 5-Aminolevulinic acid (ALA) is a potential contrast agent for fluorescence-guided surgery in pancreatic ductal adenocarcinoma (PDAC). However, factors influencing ALA uptake in PDAC have not been adequately assessed. We investigated ALA-induced porphyrin fluorescence in PDAC cell lines CFPAC-1 and PANC-1 and pancreatic ductal cell line H6c7 following incubation with 0.25–1.0 mM ALA for 4–48 h. Fluorescence was assessed qualitatively by microscopy and quantitatively by plate reader and flow cytometry. Haem bios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Publications within the last few years reflect this being the main area of research interest in terms of 5-ALA induced fluorescence in FGS, as they focus mainly on glioma surgery applications. However, initial research into PpIX accumulation in other cell lines has shown it to accumulate in cells derived from tissue such as that of melanoma [70], breast cancer [71], and lung cancer [72], with more recent work exploring it's combined use with laparoscopy for observing the spread of cancers such as gastrointestinal cancer [73], as well as its potential as a contrast agent in FGS for pancreatic cancer [74]. As 5-ALA is a relatively new probe as well as its fluorescence being outside the NIR region, its widespread use and current applications are limited and therefore considerably more research will be required for its long-term application to FGS.…”
Section: Extrinsic Probesmentioning
confidence: 99%
“…Publications within the last few years reflect this being the main area of research interest in terms of 5-ALA induced fluorescence in FGS, as they focus mainly on glioma surgery applications. However, initial research into PpIX accumulation in other cell lines has shown it to accumulate in cells derived from tissue such as that of melanoma [70], breast cancer [71], and lung cancer [72], with more recent work exploring it's combined use with laparoscopy for observing the spread of cancers such as gastrointestinal cancer [73], as well as its potential as a contrast agent in FGS for pancreatic cancer [74]. As 5-ALA is a relatively new probe as well as its fluorescence being outside the NIR region, its widespread use and current applications are limited and therefore considerably more research will be required for its long-term application to FGS.…”
Section: Extrinsic Probesmentioning
confidence: 99%
“…However, it is rather unsuitable for complete tumor delineation due to a consecutive prolongation of the surgical intervention. Therefore, numerous approaches, such as magnetic resonance imaging, ultrasound, and 5-aminolevulinic acid for fluorescence-guided surgery, are used intraoperatively mainly in a study fashion to improve delineation of several tumor entities and to optimize the extent of resection 6 . However, the precise identification of PDAC tumor borders and infiltrating areas in the retroperitoneal margin and the porto-mesenteric axis remains challenging.…”
Section: Introductionmentioning
confidence: 99%